Representation of sex workers in Malaysian news media: a critical discourse analysis - Noor, Natrah; Hamid, Bahiyah Abdul (European Publisher, 2019)
Marginalized populations such as sex workers are at constant risk of violence, abuse, and human rights violation due to inadequate laws governing their rights. Although media has an integral role in influencing the public’s perception of these vulnerable populations, it continues to reinforce social stigmas and discrimination against sex workers through stereotypical and negative representation of the populations. Drawing on Wodak’s discourse-historical approach (DHA), this paper is an outcome of a study that used the DHA analytical tools to examine the discursive strategies specifically referential, predicational and argumentative strategies employed in 20 articles relevant to sex workers in Malaysia published in The Star Online between January and December 2012. Data analysis generally revealed that the local media consistently polarised sex workers as offenders and as victims. These representations are justified and legitimized through specific linguistic devices, fallacious arguments, metaphor, and several topoi, i.e., topoi of number, blame, threat, and authority. Such representations create public intolerance towards sex workers and consequently hinder the workers' access to health care, legal and social services. This paper concludes by highlighting the contributions of the study and the need to incorporate the voices of people who work in the industry to challenge the limited representations perpetuated by the media.